Fragmented production: Regionalization of trade? - Hildegunn Kyvik Nordås (World Trade Organization (WTO), 2003)
This paper explores the impact of vertical specialization on world trade within the framework of the O-ring theory of production. Within such a framework there is little scope for substituting quantity for quality or for gaining market shares by undercutting established suppliers purely on cost. Furthermore, quality requirements will increase as lead firms in the supply chain invest in technology that reduces inventory and speeds up the production process. It is shown that potential suppliers in low-cost countries will only have an incentive to upgrade quality if adequately efficient infrastructure, logistics and customs procedures are in place. Changing trade patterns between USA and Mexico and China suggests that proximity and low trade barriers are important determinants of the extent and nature of vertical specialization. Thus, a larger share of Mexico's trade with USA is driven by vertical specialization than China's trade with USA. Nevertheless, China has caught up with Mexico as far as share in US total imports is concerned, and the market share gap has narrowed even in electronics, the sector in which vertical specialization is most prominent. It appears that vertical specialization adds to total world trade rather than replacing traditional trade flows.
Keywords: F12; F14; 330; Vertical specialization; China; Mexico; Electronics; Motor vehicles